Monitoring Obstacles of Toddlers Growth in Public Health Center Margahayu Raya Bandung City during the COVID-19 Pandemic: From Cadre Perspective - Natasya Alifah Sekarani; Dewi Marhaeni Diah Herawati; Fedri Ruluwedrata Rinawan (Althea Medical Journal, 2023)
Background:Toddler growth monitoring is one of the specific nutritional interventions used to accelerate stunting reduction. The COVID-19 pandemic has reduced various ‘Minimum Service Standards‘coverages, including toddler growth monitoring. This study aimed to explore the obstacles of toddler growth monitoring at the Integrated Service Center (Pusat pelayanan terpadu, Posyandu) during the COVID-19 pandemic. Methods: This was a qualitative study with an interpretivism paradigm. The unit of analysis was Posyandu of Margahayu Raya Public Health Center, Bandung City, West Java. Primary data were obtained through in-depth interviews with 10 cadres from different Posyandu from September-December 2021. The data were collected using a semi-structured interview guide and a recorder, and analyzed using NVivo software.Results: During the COVID-19 pandemic, toddler weighing had been suspended for several months. Starting in August 2020, cadres and public health center officers worked to ensure that toddlers’ weight, body length, and height could be monitored despite the numerous obstacles.Conclusion: The obstacles to toddler growth monitoring are inadequate instruments of toddler body height measuring during home visits, minimum cadre skills, a lack of toddlers’ mother awareness to bring their toddlers to Posyandu, and a lack of public awareness to follow health protocols.